Zakialdinn Almunthiry (D. 565 H/1258 C) "A Study of The Nature of The Translations and Their Components" - Amedi, Karavan M.A.; Khoshnaw, Hakeem A.M (Humanities Journal of University of Zakho, 2017)
ZakiAldinn Almunthiry (D. 565 H/1258 C) is one of the most popular Muslim writers and classifiers who wrote about different translations, religious bibliographies, and writers especially during the (6-7H/ 12-13C). He recorded the deaths of the people mentioned above professionally. He did not only record the lives of men, but also women who had a great role in the Islamic history and those who competed men in Qur’an, Hadith, and other fields of Language and Literature. When referring to women, he tried his best to record the news of those who were famous in science, literature, and the ones who belonged to families of mysticism and asceticism. Those women were famous in the community through their good qualities. The study aims to consider the historical translations of women objectively, who were known for their knowledge, mysticism, asceticism, and righteousness, or the ones who had a kind of political role in the Arab-Islamic world whom Almunthiry wrote about in his work on the translations and deaths. He also explained his historical vision concerning women translations and dealt with their most significant points.